1978
DOI: 10.1126/science.715440
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Insulin Into Human Cultured Lymphocytes: Electron Microscope Autoradiographic Analysis

Abstract: Electron microscope autoradiographs were prepared of IM-9 human cultured lymphocytes incubated with iodine-125-labeled insulin. With the use of [125I]insulin and Ilford L-4 emulsion, the technique had a resolution half-distance of approximately 0.085 micrometer. Autoradiographs revealed a time-dependent entry of insulin into the cell interior that was maximal after 30 minutes of incubation. At this time point nearly 40 percent of the [125I]insulin was in the interior of the cell at a distance 1 micrometer or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Morphologic evidence suggests that IM-9 lymphocytes may internalize receptor-bound insulin to some degree (17,18). However, the fact that these cells neither accumulate nor degrade appreciable amounts of 125I-insulin suggests that intracellular insulin is released intact at a rate equal to its rate of uptake or the amount of internalized insulin processed through the intracellular degradative pathway is too small to be detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphologic evidence suggests that IM-9 lymphocytes may internalize receptor-bound insulin to some degree (17,18). However, the fact that these cells neither accumulate nor degrade appreciable amounts of 125I-insulin suggests that intracellular insulin is released intact at a rate equal to its rate of uptake or the amount of internalized insulin processed through the intracellular degradative pathway is too small to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…This article must therefore be hereby marked "advertisement" in accordance with 18 reagents, and buffer were added to a total volume of 2 ml and the dishes were incubated in a shaking water bath (50 oscillations per minute). After incubation, an aliquot of the buffer was withdrawn for estimation of total radioactivity, and the remaining buffer was aspirated and discarded.…”
mentioning
confidence: 99%
“…On the basis of their studies of the binding of insulin to isolated nuclei (44) and the subcellular localization of insulin to nuclei (45), Goldfine et al (46) have suggested that insulin is internalized by the cell and recently they report that internalized insulin localizes to endoplasmic reticulum and nuclear membrane. Our studies differ in several ways for unexplained reasons: we have not found labeled insulin preferentially localized to either nuclei or endoplasmic reticulum in either cultured lymphocytes or isolated hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The fraction of bound radioactivity not dissociated by the subsequent addition of excess nonlabeled insulin may represent 1251-insulin bound irreversibly to the plasma membranes or located intracellularly, either as an intact hormone or as degradation products. Several recent studies demonstrated that insulin may enter the cells as an intact molecule, and such a process may be operative in glomerular cells (24,25).…”
Section: Discussionmentioning
confidence: 99%